Impact of androstane A- and D-ring inversion on 17β-hydroxysteroid dehydrogenase type 3 inhibitory activity, androgenic effect and metabolic stability. Issue 7 (1st April 2017) - Cortés-Benítez, Francisco; Roy, Jenny; Maltais, René; Poirier, Donald
Graphical abstract: Abstract: 17β-Hydroxysteroid dehydrogenase type 3 (17β-HSD3) is a major player in human endocrinology, being one of the most important enzymes involved in testosterone production. To capitalize on the discovery of RM-532-105, a steroidal 17β-HSD3 inhibitor, we explored the effect of its backbone configuration on inhibitory activity, androgenic profile, and metabolic stability. Two modifications that greatly alter the natural shape of steroids, i.e. inversion of the methyl on carbon 13 (13α-CH3 instead of 13β-CH3 ) and inversion of the hydrogen on carbon 5 (5β-H instead of 5α-H), were tested after the syntheses in 6 steps of 2 isomeric forms (5α/13α-RM-532-105 (6a ) and 5β/13β-RM-532-105 (6b ), respectively) of the 17β-HSD3 inhibitor RM-532-105 (5α/13β-configurations). For compound6b, a cis / trans junction of the A/B rings did not significantly alter the inhibitory activity on 17β-HSD3 (IC50  = 0.15 μM) as well as the liver microsomal stability (16.6% of6b remaining after 1 h incubation) compared to RM-532-105 (IC50  = 0.11 μM and 14.1% remaining). In contrast, a trans / cis junction of C/D rings reduced the inhibitory activity on 17β-HSD3 (IC50  = 1.09 μM) but increased the metabolic stability with 29.4% of compound6a remaining after incubation. The structural modifications represented by compounds6a and6b did not change the non-androgenicity profile of an androsterone derivative such as RM-532-105, but slightly increased its cytotoxic activity.